Land Cover Changes in Oil-Spill Affected Area: A Case Study in Pulau Rambut Wildlife Sanctuary - Anindya Putri Dewanti; Lilik Budi Prasetyo; Ani Mardiastuti (Jurnal Ilmu Pertanian Indonesia, 2026)
An offshore oil spill near Karawang, West Java, in July 2019 caused a considerable impact on the Pulau Rambut Wildlife Sanctuary, a protected area known for its mangrove ecosystems, which provide crucial habitat for waterbirds in Jakarta Bay. The purpose of this study was to map and quantify land cover types on Rambut Island, as well as examine land cover changes three years after the spill, with a focus on mangrove dynamics. Land cover categorization was performed using the Maximum Likelihood (ML) method applied to remote sensing data from SPOT-6 and SPOT-7 satellite photos for 2019, 2020, and 2021. Ground truthing and drone imagery were used to validate categorization results, and accuracy was determined using the Kappa statistics. All classes had strong levels of agreement, with Kappa values of 85.66%, 81.40%, and 82% in 2019, 2020, and 2021, respectively. Four types of land cover were identified: mangroves, non-mangrove forests, water bodies, and open spaces. Rambut Island has an expected mangrove covering of 18.80 ha in 2019, which increased to 21.15 ha in 2020 before significantly declining to 18.84 ha in 2021. These findings are consistent with field data, in which 12 of 13 MHI (Mangrove Health Index) plots were classed as moderate. This data implies that the 2019 oil spill did not result in a significant or long-term loss in mangrove area on Rambut Island.Keywords: mangrove, maximum likelihood, oil spill, Rambut Island, SPOT-6/7